Exploring gender preferences for automated teller machines (ATMS) user interface design / Kamelia Burhan - Burhan, Kamelia (2011)
Nowadays, many technological innovations rely upon user interface design to elevate their technical complexity to a usable product. User interface is the space where interaction between humans and machines occurs. The Automated Teller Machines (ATMs) has become integral part of our society. So, this research focuses on experiment about the differences between male and female on the element of the user interface design on ATMs. This research will be evaluating the element of the gender preferences on the ATM user interface design. Objective of this research is to identify the different types of design for ATMs application based on gender. Besides that, this research is to design the ATM user interface design based on gender preferences and identify the perceptions on the design on the screen of ATM. The research makes significant to the user identify their needs on the ATM application and help ATM designer to better understand what the requirement on that ATM interface design. This research will conduct survey of questionnaire by self-administered to get feedback and accurate data from the both of gender. This research will be carried out and the processes to complete the research about the gender preferences of user interface design Automated Teller Machines (ATMs). The results are graphed, analysed and comparisons made. Each menu design is evaluated. The final chapter draws conclusions from all the previous chapters and concludes if the objectives of the research were met